2013
DOI: 10.3233/dev-1312113
|View full text |Cite
|
Sign up to set email alerts
|

Internalising Problems and the Effects of Peer Ostracism on Children's Primary Needs

Abstract: The aim of this study was to examine associations between ostracism, internalising problems, and threat to primary needs (belonging, control, selfesteem, meaningful existence) in children (N = 165, M age = 9 years). Ostracism was simulated experimentally using the Cyberball paradigm-a computer-based ball-throwing game-and threats to primary needs were indexed using a modified version of the primary needs questionnaire (PNQ-C; Hawes et al., 2012). Overall, children with greater internalising problems reported g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 14 publications
2
13
0
Order By: Relevance
“…Consistent with the findings of Abrams et al () and Hawes et al (, ), Study 1 and Study 2 showed that children's moods (anger, sadness, and happiness, but not anxiety) and fundamental needs (belonging, control, meaningful existence, and self‐esteem) are strongly negatively affected when they are ostracized by a group of peers. These findings support the need‐threat model by Williams (), and show that this model can be generalized to school age children.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Consistent with the findings of Abrams et al () and Hawes et al (, ), Study 1 and Study 2 showed that children's moods (anger, sadness, and happiness, but not anxiety) and fundamental needs (belonging, control, meaningful existence, and self‐esteem) are strongly negatively affected when they are ostracized by a group of peers. These findings support the need‐threat model by Williams (), and show that this model can be generalized to school age children.…”
Section: Discussionsupporting
confidence: 85%
“…Study 1 examined the effects of ostracism on children's moods and fundamental needs when the children were either completely included or ostracized by all players. In accordance with previous research (Abrams et al, ; Hawes et al, , ), we predicted that ostracism would negatively affect mood and the four fundamental needs in children. More specifically, we expected that ostracized children would experience more anger, anxiety, and sadness, less happiness, and greater deficits in their needs for belonging, control, meaningful existence, and self‐esteem than included children.…”
Section: Introductionsupporting
confidence: 90%
See 1 more Smart Citation
“…Individual difference factors beyond age also have been studied when examining the effects of ostracism on mood and need threat in children and adolescents. For example, Hawes et al (2013) examined the association between internalizing problems and need threat in a sample of children (ages 7 through 12) using Cyberball as a manipulation of ostracism. As would be expected, children who were ostracized reported greater need threat than those who were included in the game.…”
Section: Moderating Variables Multiple Studies Have Examined Moderatmentioning
confidence: 99%
“…Specifically, these results suggest that ostracism elicits cognitions that are consistent with internalizing problems even among children who are not experiencing these problems. Thus, children's exposure to ostracism may be a risk factor for future internalizing disorders, such as depression (Hawes et al, 2013).…”
Section: Moderating Variables Multiple Studies Have Examined Moderatmentioning
confidence: 99%